PENGARUH REFORMASI BIROKRASI TERHADAP KUALITAS PELAYANAN PEMBUATAN SURAT IZIN MENGEMUDI GOLONGAN C (SIM C) PADA SAT LANTAS POLRESTA PEKANBARU - Eko Handrian (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
This study aims to determine the influence of bureaucratic reforms to service quality manufacture Driving License On Sat Then Police Pekanbaru assessment indicators used include Structuring management / Management, Reliability, responsivenes, Assurance and Empathy type of research that is located on Sat So Polresta Pekanbaru This is aidescriptive survey , namely the questionnaire as a tool to prioritize the list of data collectioniand dataicollected by theitooliisitheniused as the main raw material for analyzing the empirical condition of objectivity where the purpose of research on the location carefully. There is one group of the populationiand sample in this research that people who have been taking care of a driver's license with a total sample of 100 people. A sampling technique that is used in determining the individual sample is incidental sampling. Types and dataicollection techniquesiused consisted ofiprimary data, collected by questionnaire technique, and interviewsiand secondaryidata wasicollected using observation and documentation. While the data analysis techniques used are validity, reliability test, correlation coefficient, coefficient of determination and t test. Based on analysis techniques Correlation Coefficient for 0634, 0396 and the results of determination coefficient t test with significance <0.05 then researchers assess and conclude that there is influence of bureaucratic reform procedural aspects of the quality of service.